The diagnosis of psychopathy - Alečković Nikolić, Mila S. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
This paper analyzes the problem of the nature of the most difficult nosologic psychopathological diagnosis - psychopathy in all its features, the neurological and psychological, the social and the political. The paper also analyzes the analogy: the character of the society vis-à vis the character of the individual. In the second part, this work develops the concept of psychopathy as a general "picture of the world," a period of time and the community, with special reference to the harsh financial Darwinism and the Serbian society today (2014). The conclusion of the paper is that it is impossible to diagnose any disease as psychopathy if the psychiatric and psychological analysis does not include an analysis of sociologists, pedagogues, and especially psychologists of morality and ethicists. Finally, the attitude of the author is that every psychiatrist and psychologist who meet with psychopathy and judge it absolutely needs to know the most important ethical doctrine (deontology and utilitarianism), their opposition, as well as their consequences.